PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA DITINJAU DARI GENDER PADA MATERI PENCEMARAN LINGKUNGAN - Latifaatul Nur Azizah; Laily Rosdiana (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
The purpose of this study was to determine the effect of the application of the guided inquiry learning model in the critical thinking process and the influence of gender on student learning outcomes on environmental pollution material. The research does at SMPN 1 Ploso - Jombang. Samples use a simple random sampling technique. The number of samples used was 30 students consisting of 15 female students and 15 male students. The type of research used is pre-experimental, namely through interviews with science subject teachers and experiments with one group pretest-posttest design. The instruments used include the Learning Implementation Plan, Student Worksheets, and pretest-posttest questions. The result of this research is that there is a significant influence on the guided inquiry learning method on students' critical thinking skills. The results of the second study showed that the average N-Gain score of female students is higher. The difference in the N-Gain scores of female students and male students showed a significant difference. It means that gender affects students' critical thinking skills.